A multi-spring component modelling approach for T-stub connections. Issue 6 (June 2016) - Wang, Zhenyu; Zhang, Jinfan; Jiang, Jianqun
The connection is one of the most important members in the structural frame, and its behaviour greatly influences structural collapse patterns and anti-collapse ability. According to the concept of the component method, a semi-rigid beam-to-column connection can be defined as an assembly of a series of equivalent T-stubs and relevant components. In order to actualise the large deformation simulation of the connections, both axially and rotationally, a new multi-spring component model to evaluate properties of T-stub connections has been proposed in this article. The nonlinear property of a T-stub is described by a multi-spring system, which is used to trace the entire T-stub post-yield behaviour. A series of experiments with T-stub connections has been performed to calibrate the proposed model. The load curves and failure mode of the experiments, three-dimensional finite element method and multi-spring component modelling fit well with each other. A case study of beam-to-column semi-rigid connections has also been performed to further illustrate the usage of the T-stub component model in beam-to-column semi-rigid connections.